Elucidating the archaeal community and functional potential in two typical coastal wetlands with different stress patterns. (20th February 2021) - Chi, Zifang; Hou, Lining; Li, Huai; Li, Jiuling; Wu, Haitao; Yan, Baixing
Abstract: Archaea play dominant roles in nutrient cycling, but the archaeal community and function in coastal wetlands with different stress patterns remain poorly understood. Here, two typical coastal wetlands of the Yellow River estuary, Zone A with only tidal erosion and Zone B with runoff and tidal invasion, were selected to explore the possible differences in archaeal community and function and evaluate the influential factors. Compared with Zone B, Zone A had higher levels of total nitrogen, available phosphorous (AP) and pH. Thaumarchaeota was the most abundant archaeal phylum, followed by Euryarchaeota in Zones A and B. Candidatus_Nitrosopelagicus (30.85% in Zone A, 36.04% in Zone B) and Candidatus_Nitrosopumilus (24.10% in Zone A, 39.01% in Zone B) were the dominant ammonia-oxidizing archaea in both zones, and Haloarcula and Haloferax were the dominant denitrifying halophilic archaea in Zone A. Organisms from methanogenic genera Methanobrevibacter, Methanocorpusculum and Methanosarcina were enriched in Zone A. Anaerobic methanotrophic Candidatus_Methanoperedens (ANME-2d) had relatively low abundance in Zones A and B. These archaea were the key factors in maintaining the carbon and nitrogen cycles in coastal wetlands. Moreover, nitrification was relatively active in Zone B, and denitrification and methanogenesis dominated in Zone A. Redundancy analysis revealed that AP, NH4 + –N, pH, salinity and moisture played important roles in the determination of archaeal community composition at the genus level. Microbial community and PICRUSt analysis indicated that the archaeal communities changed significantly, but the functions were relatively stable for both zones. This finding suggests that environmental selection in similar habitats could lead to functional convergence. The relative gene abundances of nitrate reductase were relatively high, indicating that aside from denitrification, a large amount of nitrite as an electron acceptor was present to perform nitrite-driven anaerobic methane oxidation via reverse methanogenesis. The findings help in understanding the impacts of different stress patterns on archaeal community composition and functional potential in coastal wetlands. Graphical abstract: Image 1